Care seeking for under-five children and vaccine perceptions during the first two waves of the COVID-19 pandemic in Lagos State, Nigeria: a qualitative exploratory study. Issue 3 (7th March 2023) - Bakare, Ayobami Adebayo; Olojede, Omotayo E; King, Carina; Graham, Hamish; Uchendu, Obioma; Colbourn, Tim; Falade, Adegoke G; Alvesson, Helle Molsted
Abstract : Objective: To explore healthcare seeking practices for children and the context-specific direct and indirect effects of public health interventions during the first two waves of COVID-19 in Lagos State, Nigeria. We also explored decision-making around vaccine acceptance at the start of COVID-19 vaccine roll-out in Nigeria. Design, setting and participants: A qualitative explorative study involving 19 semistructured interviews with healthcare providers from public and private primary health facilities and 32 interviews with caregivers of under-five children in Lagos from December 2020 to March 2021. Participants were purposively selected from healthcare facilities to include community health workers, nurses and doctors, and interviews were conducted in quiet locations at facilities. A data-driven reflexive thematic analysis according to Braun and Clark was conducted. Findings: Two themes were developed: appropriating COVID-19 in belief systems, and ambiguity about COVID-19 preventive measures. The interpretation of COVID-19 ranged from fearful to considering it as a 'scam' or 'falsification from the government'. Underlying distrust in government fuelled COVID-19 misperceptions. Care seeking for children under five was affected, as facilities were seen as contagious places for COVID-19. Caregivers resorted to alternative care and self-management of childhood illnesses. COVID-19 vaccine hesitancy was a major concern among healthcare providers compared with community members at the time of vaccine roll-out in Lagos, Nigeria. Indirect impacts of COVID-19 lockdown included diminished household income, worsening food insecurity, mental health challenges for caregivers and reduced clinic visits for immunisation. Conclusion: The first wave of the COVID-19 pandemic in Lagos was associated with reductions in care seeking for children, clinic attendance for childhood immunisations and household income. Strengthening health and social support systems with context-specific interventions and correcting misinformation is crucial to building adaptive capacity for response to future pandemics. Trial registration number: ACTRN12621001071819.